CXCR4 positive cell‐derived Pdx1‐high/Shh‐low cells originated from embryonic stem cells improve the repair of pancreatic injury in mice. (5th May 2015) - Yu, Tao; Qing, Qing; Deng, Na; Min, Xiao‐Hui; Zhao, Li‐Na; Li, Jie‐Yao; Xia, Zhong‐Sheng; Chen, Qi‐kui
Abstract Treatments for pancreatic injuries have been significantly improved recently, but full recovery of pancreatic function remains difficult. Embryonic stem cells have great potentialities for self‐renewal and multiple differentiations. In this study, we explored an approach to induce the differentiation of pancreatic progenitor cells from embryonic stem cells in vitro. Male mouse embryonic stem cells were cultured by the hanging‐drop method to form embryoid bodies. The definitive endoderm marked by CXCR4 in embryoid bodies was sorted by magnetic activated cell sorting and subsequently administrated with b‐FGF, exendin‐4, and cyclopamine to induce the differentiation of putative pancreatic progenitor cells, which was monitored by Pdx1, and Shh expressions. The putative pancreatic progenitor cells were transplanted into female BALB/c mice with pancreatitis induced by L‐Arginine. Male donor cells were located by detecting sex‐determining region of Y‐chromosome DNA. Definitive endoderm cells (CXCR4+ cells) were sorted from 5‐day embryoid bodies. After 3‐day administration with b‐FGF, exendin‐4, and cyclopamine, Pdx1‐high/Shh‐low cells were differentiated from CXCR4+ cells. These cells developed into more amylase‐secreted cells in vitro and could specifically reside in the damaged pancreas acinar area in mice with acute pancreatitis to enhance the regeneration. The putative pancreatic progenitor cells (Pdx1‐high/Shh‐low cells) derived from mouse embryonic stem cells through the administration of b‐FGF, exendin‐4, and cyclopamine on the CXCR4+ cells in vitro could improve the regeneration of injured pancreatic acini in vivo.